2016
DOI: 10.1080/15287394.2016.1182001
|View full text |Cite
|
Sign up to set email alerts
|

Developmental neurotoxicity of polybrominated diphenyl ethers mixture de71 in Sprague-Dawley rats

Abstract: Polybrominated diphenyl ethers (PBDE) are a class of brominated flame retardants that are recognized as global environmental contaminants and a potential adverse health risk. The objective of this study was to evaluate the developmental impacts on rat Sprague-Dawley (SD) pups at postnatal day (PND) 11, 21, 50, 105, and 250 after perinatal exposure to a DE71 mixture. These PNDs corresponded to juveniles, young, and mature adults, respectively. The analysis included histopathological, transcriptional evaluation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…However, BDE congeners are still widely used as flame retardant in many household materials in countries where no apparent legislation exists . There have been a growing number of investigations regarding the neurotoxic potential of these congeners (Chen et al 2010;Giordano 2007, 2011;Goodman 2009;Gill et al 2016); these compounds are also known to produce liver damage (Cowens et al 2015;Nash et al 2013;Souza et al 2013;Zhang et al 2008a). Recently, PBDE were found to produce mitochondrial damage, which interfered in cell homeostasis (Hu et al 2007(Hu et al , 2009Pazin et al 2015;Pereira et al 2013Pereira et al , 2014Souza et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, BDE congeners are still widely used as flame retardant in many household materials in countries where no apparent legislation exists . There have been a growing number of investigations regarding the neurotoxic potential of these congeners (Chen et al 2010;Giordano 2007, 2011;Goodman 2009;Gill et al 2016); these compounds are also known to produce liver damage (Cowens et al 2015;Nash et al 2013;Souza et al 2013;Zhang et al 2008a). Recently, PBDE were found to produce mitochondrial damage, which interfered in cell homeostasis (Hu et al 2007(Hu et al , 2009Pazin et al 2015;Pereira et al 2013Pereira et al , 2014Souza et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, increasing PBDE levels in the environment and human tissue samples in the order of ng/g samples (Eskenazi et al 2013;Hites 2004;Lee et al 2013;Meironyte et al 1999) are a cause for concern. Indeed, these substances produced adverse effects including neurotoxicity, hepatotoxicity, cancer in vivo in the order of μg/g as well as following a high, single exposure dose of 10 mg/kg (Alves et al 2007;Bellinger 2013;Chen et al 2010;Costa and Giordano 2007;Cowens et al 2015;Darnerud 2003;Gill et al 2016;Nash et al 2013;Zhang et al 2008b), and in vitro cytotoxicity including the death of hepatic-derived cells in the order of micromoles (Hu et al 2009;Madia et al 2004;Souza et al 2013;Yan et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In experimental studies, PBDEs exert effects on the liver, the nervous system, and other organs; PBDEs and OH-BDEs have been associated with possible endocrine-disrupting effects (Cowens et al 2015; EFSA 2011; Gill et al 2016; Linares, Bellés, and Domingo 2015). The OH-BDE exhibit greater endocrine activity than their parent PBDE (Ptak et al 2006, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The health risk of PBDEs has recently raised global concern. PBDEs may disrupt the endocrine system, have neurodevelopment toxicity, teratogenicity and potential carcinogenicity 8 , 9 . PBDEs could affect the male reproductive function, exposure level of PBDEs in human serum is negatively associated with sperm mobility and concentration 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to 2,2′,4,4′-tetrabromodiphenyl ether (BDE-47) decreased the rate of sperm capacitation, altered sperm motility parameters and increased germ cell loss and apoptosis in both mice and rat 12 , 13 . Previous studies have shown that PBDEs with fewer bromines are more volatile and bioaccumulative 8 , 9 and hence may be more harmful to human health 14 . Mono-BDE may induce genetic recombination in mammalian cells 15 .…”
Section: Introductionmentioning
confidence: 99%